Quizartinib plus chemotherapy in newly diagnosed patients with FLT3-internal-tandem-duplication-positive acute myeloid leukaemia (QuANTUM-First): a randomised, double-blind, placebo-controlled, phase 3 trial - Erba, Harry P.; Montesinos, Pau; Kim, Hee-Je; Patkowska, Elżbieta; Vrhovac, Radovan; Žák, Pavel; Wang, Po-Nan; Mitov, Tsvetomir; Hanyok, James; Kamel, Yasser Mostafa; Rohrbach, Jaime E Connolly; Liu, Li; et al. (The lancet, 2023)
Background - Patients with acute myeloid leukaemia (AML) positive for internal tandem duplication (ITD) mutations of FLT3 have poor outcomes. Quizartinib, an oral, highly potent, selective, type 2 FLT3 inhibitor, plus chemotherapy showed antitumour activity with an acceptable safety profile in patients with FLT3-ITD-positive newly diagnosed AML. The aim of the study was to compare the effect of quizartinib versus placebo on overall survival in patients with FLT3-ITD-positive newly diagnosed AML aged 18-75 years. - Methods - We conducted a randomised, double-blind, placebo-controlled, phase 3 trial comparing quizartinib and placebo in combination with chemotherapy in induction and consolidation, followed by quizartinib or placebo single-agent continuation, in patients with FLT3-ITD-positive newly diagnosed AML at 193 hospitals and clinics in 26 countries in Europe; North America; and Asia, Australia, and South America. Patients aged 18-75 years were eligible. Patients were randomly assigned (1:1) to the quizartinib group or the placebo group by an independent biostatistician through an interactive web and voice response system, stratified by region, age, and white blood cell count at diagnosis. Patients, investigators, funders, and contract research organisations were masked to treatments assigned. Induction therapy comprised a standard 7 + 3 induction regimen of cytarabine 100 mg/m2 per day (or 200 mg/m2 per day allowed if institutional or local standard) by continuous intravenous infusion from day 1 to day 7 and anthracycline (daunorubicin 60 mg/m2 per day or idarubicin 12 mg/m2 per day) by intravenous infusion on days 1, 2, and 3, then quizartinib 40 mg orally or placebo once per day, starting on day 8, for 14 days. Patients with complete remission or complete remission with incomplete neutrophil or platelet recovery received standard consolidation with high-dose cytarabine plus quizartinib (40 mg per day orally) or placebo, allogeneic haematopoietic cell transplantation (allo-HCT), or both as consolidation therapy, followed by continuation of single-agent quizartinib or placebo for up to 3 years. The primary outcome was overall survival, defined as time from randomisation until death from any cause and assessed in the intention-to-treat population. Safety was evaluated in all patients who received at least one dose of quizartinib or placebo. This study is registered with ClinicalTrials.gov (NCT02668653). - Findings - Between Sept 27, 2016, and Aug 14, 2019, 3468 patients with AML were screened and 539 patients (294 [55%] male patients and 245 [45%] female patients) with FLT3-ITD-positive AML were included and randomly assigned to the quizartinib group (n=268) or placebo group (n=271). 148 (55%) of 268 patients in the quizartinib group and 168 (62%) of 271 patients in the placebo group discontinued the study, primarily because of death (133 [90%] of 148 in the quizartinib group vs 158 [94%] of 168 in the placebo group) or withdrawal of consent (13 [9%] of 148 in the quizartinib group vs 9 [5%] of 168 in the placebo group). Median age was 56 years (range 20-75, IQR 46·0-65·0). At a median follow-up of 39·2 months (IQR 31·9-45·8), median overall survival was 31·9 months (95% CI 21·0-not estimable) for quizartinib versus 15·1 months (13·2-26·2) for placebo (hazard ratio 0·78, 95% CI 0·62-0·98, p=0·032). Similar proportions of patients in the quizartinib and placebo groups had at least one adverse event (264 [100%] of 265 in the quizartinib group and 265 [99%] of 268 in the placebo group) and one grade 3 or higher adverse event (244 [92%] of 265 in the quizartinib group and 240 [90%] of 268 in the placebo group). The most common grade 3 or 4 adverse events were febrile neutropenia, hypokalaemia, and pneumonia in both groups and neutropenia in the quizartinib group. - Interpretation - The addition of quizartinib to standard chemotherapy with or without allo-HCT, followed by continuation monotherapy for up to 3 years, resulted in improved overall survival in adults aged 18-75 years with FLT3-ITD-positive newly diagnosed AML. Based on the results from the QuANTUM-First trial, quizartinib provides a new, effective, and generally well tolerated treatment option for adult patients with FLT3-ITD-positive newly diagnosed AML. - Funding - Daiichi Sankyo.
Online verfügbar: 25. April 2023, Artikelversion: 11. Mai 2023
Gesehen am 28.07.2023